#### Answer

(2, 1)

#### Work Step by Step

Multiply the second equation by 3
6x - 3y = 9
Add to the first equation
x + 3y = 5
6x - 3y = 9
7x = 14
x = 2
Plug x = 2 into x + 3y = 5
2 + 3y = 5
3y = 3
y = 1
Solution is (2, 1)

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

(2, 1)

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.